Application of Time-Lapse Ion Exchange Resin Sachets (TIERS) for Detecting Illegal Effluent Discharge in Mixed Industrial and Agricultural Areas, Taiwan - Shih, Po-Kang; Chiang, Li-Chi; Lin, Sheng-Chi; Chang, Tsun-Kuo; Hsu, Wei-Chan (Sustainability, 2019)
Many factories were built and scattered around the farmlands in Taiwan due to inappropriate land use planning. Illegal effluent discharge of high concentration of metals from the nearby factories has been threatening the farmlands, causing damages to agricultural production, food safety, and human health. Sampling was mostly responsible for monitoring the water quality of the agricultural environment; however, the analysis is of high cost and time consuming. Due to uneasy controlled environmental factors (i.e., illegal effluents) and time-consuming and expensive traditional analysis techniques (i.e., atomic absorption spectrometry (AAS), atomic fluorescence spectrometry (AFS), inductively coupled plasma atomic emission spectrometry (ICP-AES), inductively coupled plasma optical emission spectrometry (ICP-OES), and inductively coupled plasma mass spectrometry (ICP-MS)), we develop a fast-screening method, which is the combination of ion exchange resins and the portable X-ray fluorescence (XRF) spectroscopy to identify the source of contaminants in a mixed industrial and agricultural area in Taoyuan County, Taiwan. The time-lapse ion exchange resin sachet (TIERS) is a non-woven bag that is filled with resins and placed in the irrigation channels for continuously absorbing the metal and trace elements in water. The standardization ratios of Cu/Sr and Zn/Sr were calculated as the pollutant indicators for fast-screening the highly polluted sites of exceedance probability of 2.27% in the monitoring area. The TIERS is verified to detect the metal and trace element concentration in an efficient and sufficient way.